Bleeding complications during pregnancy and delivery in haemophilia carriers and their neonates in Western France: An observational study. Issue 6 (25th August 2020) - Nau, Alice; Gillet, Benjamin; Guillet, Benoît; Beurrier, Philippe; Ardillon, Laurent; Cussac, Vincent; Guillou, Sophie; Raj, Leela; Trossaërt, Marc; Horvais, Valérie; Bayart, Sophie; Potin, Jérôme; et al.
Abstract: Background: Pregnancy, delivery and the postpartum period expose haemophilia carriers, as well as their potentially affected neonates to a high risk of haemorrhagic complications. Objectives: To describe bleeding complications in haemophilia carriers and their newborns throughout pregnancy and postpartum and to identify potential factors increasing the risk of bleeding in this population. Patients/Methods: The ECHANGE multicentre observational cohort study was conducted between January 2014 and February 2019 using the BERHLINGO database comprised of patients from seven French haemophilia centres. Results: During the 5 years study period, a total of 104 haemophilia carriers and 119 neonates were included, representing 124 pregnancies and 117 deliveries. Thirty‐five (30%) bleeding events were observed, most of them (83%) occurred during the postpartum period, and 37% were reported during the secondary postpartum. Neuraxial anaesthesia was not complicated by spinal haematoma. Three (2.5%) neonates experienced cerebral bleeding. Caesarean section was associated with an increased risk of maternal bleeding in primary and secondary postpartum periods. Basal factor level <0.4 IU/mL was also found to be associated with an increased risk of bleeding during secondary postpartum. Conclusion: In our cohort, bleeding events occurred in more than a third of haemophilia carriers mainly in the postpartum period, and a significant portion of this bleeding occurred during the secondary postpartum. Haemophilia carriers warrant specific attention during primary and secondary postpartum, in particular in case of caesarean section and low basal factor level. The ECHANGE study is registered at clinicaltrials.gov identifier: NCT03360149.